Судові рішення в цивільному процесі України - Андронов, Ігор Володимирович; Андронов, Игорь Владимирович; Andronov, Igor V. (My University, 2018)
Дисертація на здобуття наукового ступеня доктора юридичних наук за спеціальністю 12.00.03 – цивільне право і процес; сімейне право; міжнародне приватне право. – Національний університет «Одеська юридична академія», Одеса, 2018. Дисертація є першим у вітчизняній науці цивільного процесуального права спеціальним комплексним дослідженням теоретичних та практичних проблем ухвалення, проголошення та набрання законної сили судових рішень у цивільному процесі України в умовах оновленого цивільного процесуального законодавства та євроінтеграційних процесів. У дисертації надано оцінку стану дослідження та наявних в науці цивільного процесуального права тенденцій щодо формування вчення про судові рішення в цивільному процесі та систематизовано існуючі методологічні підходи до їх наукового дослідження. Визначено поняття, сутність та види судових рішень як актів правосуддя в цивільному процесі, вдосконалено систему вимог, що пред’являються до судових рішень в цивільному процесі, охарактеризовано юридичну природу законної сили судових рішень, розкрито сутність рішення суду першої інстанції, уточнено зміст основних вимог, що пред’являються до рішення суду як процесуального документа, та адаптовано їх до існуючих європейських стандартів судочинства, диференційовано судові рішення в цивільному процесі, визначено в їх системі місце кожного з видів судових рішень та на цій основі класифіковано судові рішення. Розглянуто властивості судових рішень, що набрали законної сили, та окреслено межі дії законної сили судових рішень. З’ясовано зміст поняття судових ухвал та здійснено їх класифікацію. Розкрито сутність концепції законної сили судових ухвал. Охарактеризовано юридичну природу судового наказу. Виокремлено процесуальні особливості набрання судовим наказом законної сили. Визначено поняття та сутність постанов судів апеляційної та касаційної інстанції як актів правосуддя, виявлено специфіку обов’язковості постанов Верховного Суду. Сформульовано практичні рекомендації щодо складення тексту судових рішень на основі здійснення аналізу форми та змісту кожного з видів судових рішень. Розроблено науково обґрунтовані пропозиції щодо вдосконалення правового регулювання порядку ухвалення та проголошення судових рішень в цивільному процесі, набрання ними законної сили.

Диссертация на соискание научной степени доктора юридических наук по специальности 12.00.03 – гражданское право и процесс; семейное право; международное частное право. – Национальный университет «Одесская юридическая академия», Одесса, 2018. Диссертация является первым в отечественной науке гражданского процессуального права специальным комплексным исследованием теоретических и практических проблем принятия, оглашения и вступления законную силу судебных решений в гражданском процессе Украины в условиях обновленного гражданского процессуального законодательства и евроинтеграционных процессов. Определены понятие, сущность и виды судебных решений как актов правосудия в гражданском процессе, усовершенствована система требований, предъявляемых к судебным решениям в гражданском процессе, охарактеризована юридическая природа законной силы судебных решений, раскрыта сущность решения суда первой инстанции, уточнено содержание основных требований, предъявляемых к решению суда как процессуальному документу, и осуществлена их адаптация к существующим европейским стандартам судопроизводства, дифференцированы судебные решения в гражданском процессе, определенно в их системе место каждого из видов судебных решений и на этой основе судебные решения классифицированы. В диссертации представлена оценка состояния исследования, а также имеющихся в науке гражданского процессуального права тенденций относительно формирования учения о судебных решениях в гражданском процессе и систематизированы существующие методологические подходы к их научному исследованию. Рассмотрены свойства судебных решений, вступивших в законную силу, очерчены пределы действия законной силы судебных решений. Определено содержание понятия судебных определений и осуществлена их классификация, Раскрыто содержание концепции законной силы судебных определений. Охарактеризована юридическая природа судебного приказа. Выделены процессуальные особенности вступления судебных приказов в законную силу. Определено понятие и сущность постановлений судов апелляционной и кассационной инстанции как актов правосудия, выявлена специфика обязательности постановлений Верховного Суда. Сформулированы практические рекомендации относительно составления текста судебных решений на основе осуществления анализа формы и содержания каждого из видов судебных решений. Разработаны научно обоснованные предложения по совершенствованию правового регулирования порядка вынесения и оглашения судебных решений в гражданском процессе, вступления их в законную силу.

The Thesis for the Degree of Doctor of Law in Specialty 12.00.03 – Civil Law and Civil Procedure; Family Law; International Private Law. – National University “Odessa Law Academy”, Odessa, 2018. The thesis is the first in the science of civil procedural law special complex research theoretical and practical issues of adoption, announcement and entry into force of court decisions in civil proceedings of Ukraine in the context of renewed civil procedural legislation and European integration processes. The new conceptual approach to determining the essence of court decisions in civil proceedings in the context of their role in the implementation of the main function of the judicial authorities – the administration of justice are proposed in the thesis. Consideration of justice in civil cases as an inseparable unity of law enforcement activities of courts and the result of judicial enforcement in the process of resolving civil cases, which consists in protecting the violated subjective substantive right or the legally protected interest of a particular person as a result of court resolution of a legal dispute based on the rule of law was proposed. One of the main distinguishing features of justice is such a specific characteristic as the availability of judicial discretion, which is an essential tool of solving legal conflicts which are the subject of litigation. Also an essential feature of the court decision as an act of justice is its compliance with the rule of law. Illegal decision, although it is a procedural document form, cannot be considered as an act of justice, because justice means «judged on law», and if the decision was taken contrary to the laws, it does not fulfill its purpose and not directed to perform the tasks of civil procedure. The judgment in civil procedure (in the sense of it as a generic term for all acts of justice, taken in civil procedure) – is a judicial act that in the appropriate procedural form contains judicial findings, based on the rule of law, on specific legal question put before the court during the consideration and resolution of civil cases. It is exactly the result of judicial enforcement that is decisive in the essential characteristic of justice. Therefore, only those court decisions are acts of justice that embody this positive result of resolving a legal dispute, which 42 manifests itself in individual legal regulatory influence on public relations that were the subject of judicial proceedings. The concept, nature and types of court decisions as acts of justice in civil proceedings have been defined, the system of requirements for court decisions in civil proceedings has been improved. The legal nature of the legal force of court decisions was characterized, the essence of the decision of the court of first instance was revealed, the content of the main requirements for the court decision as a procedural document was clarified and adapted to the existing European standards of legal proceedings, court decisions in civil procedure were differentiated, the place of each type of court decisions is defined in their system and on this basis court decisions are classified. The assessment of the state of the research, as well as the trends existing in the science of civil procedural law regarding the formation of the theory of court decisions in civil proceedings are presented in the thesis and the existing methodological approaches to their scientific research are systematized. The properties of court decisions that entered into legal force were also reviewed in the thesis, the limits of validity of court decisions were outlined, the concept of judicial definitions was revealed and classified, the concept of legal force of court definitions was analyzed, the legal nature of a court order was outlined, the procedural features of court orders entry into force were outlined. The concept and essence of the decisions of the courts of appeal and cassation instances as acts of justice were determined, the specificity of the binding decisions of the Supreme Court was revealed. Practical recommendations regarding the compilation of the text of court decisions based on the analysis of the form and content of each type of court decision are formulated. Scientifically grounded proposals for the improvement of legal regulation of issues related to the adoption and announcement of court decisions in civil proceedings, and their entry into force have been developed.
дис. ... доктора юрид. наук: 12.00.03
Андронов І.В. Судові рішення в цивільному процесі України: дис. ... доктора юрид. наук: 12.00.03 / Андронов Ігор Володимирович. - Одеса, 2018. - 435 с.
Keywords: суд; правосуддя; судочинство; цивільний процес; судовий акт; судове рішення; судова ухвала; судовий наказ; судова постанова; законна сила судового рішення; правосудие; судопроизводство; гражданский процесс; судебный акт; судебное решение; судебное определение; судебный приказ; судебное постановление; законная сила судебного решения; court; justice; legal proceedings; civil process; civil act; court decision; judicial definition; court order; court decree; legal force of the court decision